SITUAÇÃO DE VIDA DE CRIANÇAS EM VULNERABILIDADE SOCIAL EM PERÍODO DE PANDEMIA: SUBSÍDIOS PARA CRIAÇÃO DE ESTRATÉGIAS PROTETIVAS - Araújo, Denise Flores (2022)
The situation of families in social vulnerability is a reality in the Brazilian context. In the scenario of inequality, adults, elderly, young people and children appear, however it is in childhood that vulnerability is established in a more perverse way. Families are structured economically and socially, they allow children to expand their skills and competences, improving the quality of childhood life. With the increase in child violence due to the social isolation caused by the new coronavirus pandemic, there is a need to expand the look at the child in their social context. Therefore, one of the processes that have contributed to the improvement of the living situation and the development of low-income communities are health promotion actions, obtained through Social Technologies such as Non-Governmental Organizations (NGOs), which help in the prevention, protection and care of subjects living in fragile contexts. Objectives: To assess the life situation of children and families in social vulnerability during a pandemic and create proposals for protection strategies that can be implemented in the work of an NGO with this population. Methodology: This is a qualitative, descriptive and exploratory research. The research was carried out in an NGO that assists children in social vulnerability, in a municipality in the interior of RS. The questionnaire was applied to 10 parents/caregivers and 10 children and the Children's Quality of Life Self-Questionnaire (AUQEI) was applied to assess the children's QOL. After data collection, the meeting was held with the institution's technical team, in which intervention strategies were outlined in view of the demands identified by the research. Results: The results are presented in the format of two manuscripts. The first considers the development of scientific production. This indicated a context of suffering in families with violence, chemical dependence, illness and lack of resources in the homes of the children and family members interviewed. Based on these results, protective strategies were created with the NGO team for application in this population, which gave rise to the second manuscript. The main strategies listed were the following: 1) Approaching and caring for families; 2) Health education; 3) Combat violence and child labor; 4) Specialized attention. Conclusion: In this way, it is that strategies to protect children in situations of social vulnerability are important tools for coping with situations of risk to childhood that can instrumentalize Social Technologies, such as NGOs, in promoting quality of life for children and adolescents. Technical Product and its applicability: The technical product of this dissertation was called "Strategies for the Protection of Children and Families in Social Vulnerability" and has the purpose of serving as support for actions carried out in the participating NGO in order to seek to solve the problems identified in the present study.